Readiness (Kesiapan Belajar) dalam Perspektif Psikologi Pendidikan Islam: Kajian Deskriptif Terhadap Konsep, Faktor dan Implikasinya - Fitri Anita; Delfi Yatri; Erna Yulis; Ismail Syakban; Julhadi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the concept of learning readiness from the perspective of Islamic educational psychology through a qualitative descriptive approach. The method used is library research by reviewing various scientific sources in the form of books, journal articles, and relevant academic documents in the last five years. Data were collected through documentation techniques and analyzed using content analysis through the stages of data reduction, classification, interpretation, and drawing conclusions. The results of the study indicate that learning readiness from an Islamic perspective encompasses not only physical and intellectual readiness, but also emotional, social, and spiritual readiness of students. The concept of learning readiness in Islamic education is based on the values ​​of tazkiyatun nafs, sincerity of intention, and the formation of morals in the process of seeking knowledge. Factors that influence learning readiness include physical and psychological conditions, the learning environment, previous experiences, motivation, and spirituality. The implications of this study emphasize that the learning process in Islamic education needs to pay attention to student readiness holistically through adaptive learning strategies, providing motivation, and strengthening spiritual values. This study is expected to enrich the study of Islamic educational psychology, particularly regarding the concept of integrative and humanistic learning readiness.